Late Holocene environmental changes reconstructed from stable isotope and geochemical records from a cushion-plant peatland in the Chilean Central Andes (27°S) - Kock, Sebastian T.; Schittek, Karsten; Mächtle, Bertil (Journal of quaternary science, 2019)
A Late Holocene paleoenvironmental record was obtained from the Lagunillas cushion peatland (LP, 27°12′S, 69°17′W), located in the dry Puna of the western Central Andes. Ten radiocarbon dates build the chronology for the last 1800 cal a BP. Analyses of stable isotopes on cellulose (δ18Ocell, δ13Ccell) and geochemical proxies on organic matter (δ13COM, δ15Nbulk, TOC, TN, LOI, T535) were conducted to identify major paleoenvironmental changes in this record. Simultaneously, ambient water (δ18O, δ2H) and plant samples of the dominant species Oxychloe andina (δ18Ocell, δ13Ccell) reveal insights into modern conditions. The record reveals distinct multi-centennial oscillations of peat layer thickness and δ18Ocell. Decomposition, changes in the dominating plant species as well as in plant parts (leaves/roots) can be excluded as driving factors for these oscillations. Thus, δ18Ocell seems to be externally forced and reflects humidity changes. Around 470 cal a BP a distinct change towards increased humidity occurred, lasting during the Little Ice Age until about 70 cal a BP. Humid conditions prevailed between 1530 and 1270 cal a BP. Increasing δ18Ocell values since 30 cal a BP mark a trend towards again increased aridity.
Gesehen am 16.09.2019